Addressing eating disorders through legislation: The Israeli 'Models' Law'-process, enactment, and dilemmas - Yael Latzer; Rachel Adatto; Dianne Neumark-Sztainer (Elsevier, 2022)
Preventing the onset of eating disorders and disordered eating pathology is crucial. While these conditions have a multi-factorial etiology, socio-cultural norms, particularly the media, contribute greatly. Policy and legislative action are warranted to change harmful media images. To the best of our knowledge, Israel was the first country to tackle the problem of unrealistic and unhealthy images in the media through legislation by initiating and passing an innovative law. The "Knesset," the Israeli Parliament, voted in December 2012 to pass new legislation that forbids the appearance of underweight models (BMI of 18.5 or less) in commercial advertising. The law further requires that if a graphic editing program has been used to reduce the dimensions of a model in advertising photographs, this fact must be clearly indicated. The purpose of this article is to describe the law; the process and obstacles to creating and passing the law in the Knesset; national and international reactions to this Israeli law; and the challenges of implementing (enacting and enforcing) this law in Israel. Given that other countries are implementing similar policies, additional legal approaches are described, including ideas for further research on how to enact, enforce, and evaluate the impact of such laws.